Evaluation Human Resources Information System Using COBIT 5 Framework in Technology Insurance Company - Alexandro Afredo Louis; Melissa Indah Fianty (G-Tech: Jurnal Teknologi Terapan, 2023)
Technology insurance companies experience problems with HRIS (Human Resources Information System), where there is no SOP in handling process problems and the risk of handling server problems and data operations that cause data leakage crimes in the HRIS system within the company. The problems are evaluated for governance using COBIT 5 as a framework. There are four selected domains, EDM04, APO07, APO12, and DSS03, based on the COBIT 5 Analysis process, which is adjusted to the problem. Data were collected through interviews with business, IT, management, and company directors. The results are at capability level 1. The EDM04 process gets an average of 73.44%, the APO07 process gets an average of 68.8%, the APO12 process gets an average of 57.36%, and the DSS03 process gets 59.7%, where the target company is level 2. The recommendations aim to increase the level of capability to the level targeted by the company.